Renewing terraces and drystone walls of Algarvian Barrocal. Cultural and touristic values - Marçal Gonçalves, Marta (2018)
This paper aims to enhance the functions of terraces and drystone walls as structural elements and distinctive factors of the traditional rural zone known as the barrocal of the Algarve, south of Portugal. In fact, such elements define the character of the landscape that forms the background of a traditional touristic region along the coast. The core of this paper will be the knowledge of construc-tion processes, spatial distribution, and hydrological, ecological, economic and social functions, once it is quite necessary for the Algarve region. Some projects and studies have been developed in the Mediterranean context, but there is not enough research on this subject in the south of Portugal. Secondly, the social meaning, or acknowledgement of the landscape characterized by drystone wall structures, will be the key for finding real possibilities of renewing the terraces. Therefore, the landscape will be assumed as a common good. In this subject, we take into account the potential role and sensibility of tourists and resident popu-lation. Beyond static patrimonial statutes, we can design some practical possibil-ities to enhance plastic features and new uses leading to an acknowledgement of the Algarvian drystone wall structure, referred as a part of Mediterranean coastal landscapes. Some examples that can add cultural and touristic value could be: recreation areas for urbanites, new cooperative forms of agriculture, hobby farm-ing, workshops about harvesting traditional products, circuits and pedestrian paths, and interchange with similar Mediterranean regions defining broader cir-cuits.